2019
DOI: 10.3390/nu11061293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Degree of Polymerization of Fructans on Ex Vivo Fermented Human Gut Microbiome

Abstract: Prebiotic supplements are used to promote gastrointestinal health by stimulating beneficial bacteria. The aim of this study was to compare the potential prebiotic effects of fructans with increasing degrees of polymerization, namely fructooligosaccharides (FOS) and inulins with a low and high polymerization degree (LPDI and HPDI, respectively), using an ex vivo fermentation system to simulate the colonic environment. The system was inoculated with pooled feces from three healthy donors with the same baseline e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…NCD, normal chow diet; HFD, high-fat diet; SC, high-fat diet plus short-chain inulin; LC, high-fat diet plus long-chain inulin. (2020) 10:978 | https://doi.org/10.1038/s41598-020-58048-w www.nature.com/scientificreports www.nature.com/scientificreports/ SCFAs compared with that of the SC inulin intervention, which was consistent with the report that higher polymerization indicates higher acidification activity than lower polymerization in ex vivo fermentation 32 . Moreover, there was a significant difference in gut microbial communities between the SC and LC groups ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…NCD, normal chow diet; HFD, high-fat diet; SC, high-fat diet plus short-chain inulin; LC, high-fat diet plus long-chain inulin. (2020) 10:978 | https://doi.org/10.1038/s41598-020-58048-w www.nature.com/scientificreports www.nature.com/scientificreports/ SCFAs compared with that of the SC inulin intervention, which was consistent with the report that higher polymerization indicates higher acidification activity than lower polymerization in ex vivo fermentation 32 . Moreover, there was a significant difference in gut microbial communities between the SC and LC groups ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, other studies showed that there is no impact of inulin supplementation of HFD on food intake [ 25 ] while others reported that food intake in mice fed HFD plus long-chain inulin was higher than those of mice fed HFD and HFD plus short-chain inulin [ 19 ]. Several studies suggest that the anti-obesogenic effects of inulin depend on the dietary dosage or the degree of polymerization, which are factors that could influence its fermentation into SCFA by the gut microbiota [ 18 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that bacterial growth increased with the decrease in DP, which was consistent with our previous report, 25 but opposed to the result of CPPN and CTPN. Previous studies also showed that when DP increased, the prebiotic bioactivity also improved 62–65 . This discrepancy may prove that DP is not the sole determinant of prebiotic bioactivity of these polysaccharides.…”
Section: Resultsmentioning
confidence: 88%